C–S Bond Alkynylation of Diaryl Sulfoxides with Terminal Alkynes by Means of a Palladium–NHC Catalyst - Yoshida, Yuto; Nogi, Keisuke; Yorimitsu, Hideki (Synlett, 2017)
Sonogashira–Hagihara-type alkynylation of diaryl sulfoxides with unactivated terminal alkynes has been developed. With a combination of a palladium–NHC catalyst and LiOtBu as a base, a series of diaryl sulfoxides were converted into the alkynylated products via C–S bond cleavage.
Keywords: C–S bond alkynylation; palladium catalyst; aryl sulfoxide; alkyne